Productivity of Labour and Salaries in Russia: Problems and Solutions - Vaisburd, Victor A.; Simonova, Marina V.; Bogatyreva, Irina V.; Vanina, Ella G.; Zheleznikova, Elena P. (International Journal of Economics and Financial Issues, 2016)
The article gives the analysis of the level and dynamics of productivity of labour in the economy of Russia in general and Samara Region in particular; the ratio of labour productivity increase and salaries. It considers why Russia is lagging behind the developed countries in terms of the level of labour productivity and justifies the necessity of the development of the mechanism of labour productivity management and the feasibility of the relevant laws. It also reveals the drawbacks of the Labour Legislation in the sphere of salaries and the absence of clear definitions of such concepts as salary, salary payment and minimal salary in it. The article studies the problem of fictitious piecework as the result of imperfect organization of salaries payment. The authors substantiate the increase of tariff rates and salaries, the use of reasonable labour standards and the right choice of forms and systems of payment are the interconnected elements of the rational organization of payment which is an important factor of labour productivity increase and production efficiency. The authors suggested their own definition of the “salary” concept. They studied the modern approaches to labour payment in Russia and abroad, its structure and the principles of formation of minimal salary. It was proved that minimal salary should not be less than minimal living wage and should be even higher bearing in mind family burden. On the bases of the data presented we stated that the level of salaries in Russia is to a great extent predetermined by the absence of clear state policy on the problem of the essence, purposes and the size of minimal salary. It was revealed that the correspondent advance coefficients (the ratio of labour productivity growth to the rate of wage growth) are stably low and the coefficients of wage capacity (the ratio of wage growth to the rate of growth of labour productivity) are high. The conclusion of non-compliance of wage growth and the corresponding (advancing) growth of labour productivity is made, which can justify the need for a law (or laws) on labour productivity and wages. We suppose it is necessary to give clear definitions of such socially important categories as minimal living wage, minimal salary, minimal basic salary rates and logic links between them in the Labour Code which will facilitate the development of labour relations and effective organization of salary payment. Keywords: Productivity of labour; Salary; Salary payment; Ratio of labour productivity growth to the rate of wage growth; Productivity factors; Minimal salary; Forms and systems of salary payment; Setting of labour quotas; Fictitious piecework. JEL Classifications: J24; J30; J31